A new method for the estimation of olive oil healthfulness - Karkoula, E.a; Melliou, E.b; Magiatis, P.a (International News on Fats, Oils and Related Materials, 2013)
Several epidemiological studies have shown that the traditional Mediterranean diet is associated with a lower incidence of atherosclerosis, cardiovascular disease, neurodegenerative diseases, and certain kinds of cancer. These appreciable health-promoting properties have been partially correlated with the regular consumption of extra virgin olive oil as the principal source of fat. Olive oil is the most famous agricultural product in the Mediterranean, with a history as old as that region’s civilization. Olive fruits and olive oil not only are delicious but also have been considered as medicines since ancient times.
cited By (since 1996)0